Mechanism of Visible-Light Photooxidative Demethylation of Toluidine Blue O - Zúñiga-Núñez, D; Barrías-González, P (American Chemical Society, 2019)
Experiments and theoretical calculations by density functional theory (DFT) have been carried out to examine a self-sensitized type I photooxidation of toluidine blue O (TBO+). This study attempts to build a connection between visible-light photolysis and demethylation processes of methylamine compounds, such as TBO+. We show that controlled photoinduced mono- and double-demethylation of TBO+ can be achieved. The kinetics for the appearance rate of the mono-demethylated TBO+ and the double-demethylated TBO+ were found to fit pseudo-first-order kinetics. DFT calculations have been used to examine the demethylation of TBO+ and included N,N-dimethylaniline as a model compound for TBO+. The results show an oxygen-dependent demethylation process. The mechanism for the sequential methyl loss is proposed to be due to H• or e-/H+ transfer to 3TBO+∗ followed by a reaction of TBO+• with O2, yielding a C-peroxyTBO+• intermediate. Instead of aminyl radical peroxyl formation, i.e., N-peroxyTBO+•, the C-centered peroxyTBO+• is favored, that upon dimerization (Russell mechanism) leads to dissociation of formaldehyde from the methylamine site. © 2019 American Chemical Society.